Perceived Barriers to Online Collaborative Learning by Prospective EFL Teachers - Kasyfur Rahman; Hatomi Hatomi (Metathesis: Journal of English Language, Literature, and Teaching, 2021)
This research aims to unveil the types of online collaborative learning activities undertaken by prospective EFL teachers in one of Indonesian universities located in West Nusa Tenggara Province, along with the barriers to such learning environment and their sources. This research employed mixed-method research with explanatory sequential design and to collect the data, a survey with 41-item questionnaire developed based on six constructs derived from previous research entailing motivation, commitment, social interaction, technical skills, time and support and technical problems distributed to 53 respondents and a semi-structured interview administered to 10 selected interviewees to elicit deeper information on the perceived barriers. Data analysis executed using descriptive statistics and thematic analysis suggests that most of the respondents utilized learning management system and WhatsApp group to carry out collaborative learning tasks. They also reported that the mostly undertaken collaborative activities entail group projects, group discussion, group presentation, and knowledge sharing. In addition, while generally the respondents select neutral responses across all the construct, there is a constant higher refusal than agreement rates to the barriers in all constructs except for the technical problems. This further implies that the barriers on the online collaborative learning depends on several factors and all these constructs are mutually interconnected.